Import Sourcing Dynamics: An Integrative Perspective - Swamidass, Paul M. (Journal of International Business Studies, 1993)
The character of import sourcing for manufacturing has changed beyond the reach of current explanatory schemes. This study knits several evolving trends in the area of import sourcing into a theoretical framework in order to facilitate research in this under-researched topic and expose to practitioners the increasing strategic value of import sourcing.